The molecular architecture of the nuclear pore complex - Alber, Frank; Devos, Damien (Nature, 2007)
Nuclear pore complexes (NPCs) are proteinaceous assemblies of approximately 50 MDa that selectively transport cargoes across the nuclear envelope. To determine the molecular architecture of the yeast NPC, we collected a diverse set of biophysical and proteomic data, and developed a method for using these data to localize the NPC's 456 constituent proteins (see the accompanying paper). Our structure reveals that half of the NPC is made up of a core scaffold, which is structurally analogous to vesicle-coating complexes. This scaffold forms an interlaced network that coats the entire curved surface of the nuclear envelope membrane within which the NPC is embedded. The selective barrier for transport is formed by large numbers of proteins with disordered regions that line the inner face of the scaffold. The NPC consists of only a few structural modules that resemble each other in terms of the configuration of their homologous constituents, the most striking of these being a 16-fold repetition of 'columns'. These findings provide clues to the evolutionary origins of the NPC.